2015
DOI: 10.9734/ajaees/2015/15178
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Kenyan Youth’s Perception towards Agriculture and Necessary Interventions; a Review

Abstract: Approximately 64% of unemployed persons in Kenya are youth, most of which live in rural areas and lacks formal education and vocational or professional skills. In spite of this, youth participation in agriculture has been relatively low in the country. This may be partly attributed to, among other factors, thepoor perception of the youth on agriculture. Agriculture which is basically a ruraloriented sector remains the backbone of the Kenya's economy contributing over 30% of GDP. The sector provides over 80% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 3 publications
0
19
0
2
Order By: Relevance
“…Pencapaian maksud tersebut, maka sasarannya adalah generasi muda pertanian terutama petani muda. Optimisme perlu dibangun dengan pandangan bahwa dengan membina petani muda agar berjiwa agribisnis (wirausaha) sehingga pembangunan sektor pertanian akan tetap berlanjut (Njeru, 2015). Hal ini berarti perlu adanya peningkatan kompetensi petani muda dalam mengakses teknologi, modal, pasar dan manajemen sehingga menjadi petani muda wirausaha mandiri yang inovatif, kreatif, mampu bersaing, berwawasan global dan professional (PERMENTAN No.…”
Section: Pembangunanunclassified
“…Pencapaian maksud tersebut, maka sasarannya adalah generasi muda pertanian terutama petani muda. Optimisme perlu dibangun dengan pandangan bahwa dengan membina petani muda agar berjiwa agribisnis (wirausaha) sehingga pembangunan sektor pertanian akan tetap berlanjut (Njeru, 2015). Hal ini berarti perlu adanya peningkatan kompetensi petani muda dalam mengakses teknologi, modal, pasar dan manajemen sehingga menjadi petani muda wirausaha mandiri yang inovatif, kreatif, mampu bersaing, berwawasan global dan professional (PERMENTAN No.…”
Section: Pembangunanunclassified
“…The study findings also agree with those of Brooks et al (2012) who found that if youth's contribution is matched with the right skills and resources, the much needed youth potential in agricultural sector could be realized. But, as Njeru et al (2015) and Noorani (2015) contends, lack of incentives and drudgery are some of the reasons why youth are disinterested in agriculture and that in most parts of the world, agriculture is seen as a less worthwhile subject or as a last resort for under-achievers. These study findings are supported by Brooks et al (2013) and Noorani (2015) that agriculture in Kenya is not the thing to do unless everything else fails and it is not perceived by many as an activity that provides a good standard of living (Leavy & Hossain, 2014).…”
Section: Correlation Measure For Youth Perception Of Agriculture and mentioning
confidence: 99%
“…Evidence in East Africa also shows that the status of agriculture as "a poor man's job" is further reinforced in schools when students are sent to dig the school farm as a form of punishment for a mistake. Instead, salaried employment in the formal sector is promoted and portrayed as a prestigious occupation with high esteem (Njeru et al, 2015).…”
Section: Correlation Measure For Youth Perception Of Agriculture and mentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of a country's population comes along with it food security challenges, because environmental resources must be over tapped to meet up with needs of the population Encouraging the youth who are highly dynamic and flexible could lead to agricultural development (Njeru, 2017) and consequently food security. Being one of such developments, some authors emphasized the need to include agriculture in primary school curriculum to enable teachers to instill a positive perception in students by explaining the many aspects of agriculture; its importance in everyday life; and inherent career opportunities to the youth (Njeru et al, 2015). That entails providing a sound background for the up-growing youth to be partakers in agricultural education where they could play their roles effectively.…”
Section: Introductionmentioning
confidence: 99%